Constraints on the Electron Acceleration Process in Solar Flare: A Case Study - G. Li; X. Wu; F. Effenberger; L. Zhao; S. Lesage; N. Bian; L. Wang (Geophysical Research Letters)
Abstract Combining in situ measurements of energetic electrons and remote sensing observations of hard X‐rays and type III radio bursts, we examine the release times of energetic electrons in the July 23, 2016 event. We find that the releases of in situ energetic electrons from the Sun are delayed from those electrons that are responsible for the hard X‐rays. We further find that the release time of in situ electrons is a function of electron energy. Under the assumption that the acceleration mechanism for the upward propagating electrons is of Fermi‐type and is controlled by an energy‐dependent diffusion coefficient, we fit these release times by a simple functional form, related to the turbulence spectral index. Implications of our study on the underlying electron acceleration mechanisms and the magnetic reconnection process in solar flares are discussed. Our results demonstrate the power of the recently developed fractional velocity dispersion analysis (FVDA) method in solar flare studies.